factorise :
1) (m+2n) (3m+4n) - (2m-3m) (m+2n) + (m +2n)²
2) 10 - 13x - 9x²
Answers
Answered by
3
Answer:
(3m-2n) (2m-3n)
= 3m ( 2m-3n) -2n (2m-3n)
= 3m × 2m - 3m × 3n - 2n × 2m + 2n × 3n
= 6m² - 9mn - 4mn + 6n²
= 6m² - 13mn + 6n²
When m = 1, n = -1, we get
(3m -2n ) (2m - 3n)
= 6m² - 13mn + 6n²
= 6 × (1)² - 13 × 1 × (-1) + 6 × (-1)² = 6 + 13 + 6 = 25
Hope it helped
☺☺☺☺
acobdarfq and 25 more users found this answer helpful
THANKS
15
4.1
(10 votes)
Log in to add comment
Answer
3.3/5
2
SomeoneVerySpecial
Ace
1.2K answers
411.9K people helped
HERE IS THE ANSWER TO YOUR QUESTION!!
We have;
(3m-2n) (2m-3n)
=> 3m ( 2m-3n) -2n (2m-3n)
=> 3m × 2m - 3m × 3n - 2n × 2m + 2n × 3n
=> 6m² - 9mn - 4mn + 6n²
=> 6m² - 13mn + 6n²
When m = 1, n = -1, we get
(3m -2n ) (2m - 3n)
=> 6m² - 13mn + 6n²
= 6 × (1)² - 13× 1× (-1) +6 × (-1)² = 6 + 13 + 6 = 25
HOPE IT HELPED!!
Similar questions